Gas exchange and ventilation during dormancy in the tegu lizard Tupinambis merianae - De Andrade, Denis Vieira [UNESP] (1999)
The tegu lizard Tupinambis merianae exhibits an episodic ventilatory pattern when dormant at 17 °C but a uniform ventilatory pattern when dormant at 25 °C. At 17 °C, ventilatory episodes were composed of 1-22 breaths interspaced by non-ventilatory periods lasting 1.8-26 min. Dormancy at the higher body temperature was accompanied by higher rates of O2 consumption and ventilation. The increase in ventilation was due only to increases in breathing frequency with no change observed in tidal volume. The air convection requirement for O2 did not differ at the two body temperatures. The respiratory quotient was 0.8 at 17 °C and 1.0 at 25 °C. We found no consistent relationship between expired gas composition and the start/end of the ventilatory period during episodic breathing at 17 °C. However, following non-ventilatory periods of increasing duration, there was an increase in the pulmonary O2 extraction that was not coupled to an equivalent increase in elimination of CO2 from the lungs. None of the changes in the variables studied could alone explain the initiation/termination of episodic ventilation in the tegus, suggesting that breathing episodes are shaped by a complex interaction between many variables. The estimated oxidative cost of breathing in dormant tegus at 17 °C was equivalent to 52.3 % of the total metabolic rate, indicating that breathing is the most costly activity during dormancy.